Promising AAV.U7snRNAs vectors targeting DMPK improve DM1 hallmarks in patient-derived cell lines - Almeida, Camila F.; Robriquet, Florence; Vetter, Tatyana A.; Huang, Nianyuan; Neinast, Reid; Hernandez-Rosario, Lumariz; Rajakumar, Dhanarajan; Arnold, W. David; McBride, Kim L.; Flanigan, Kevin M.; Weiss, Robert B.; Wein, Nicolas (Frontiers in Cell and Developmental Biology, 2023)
Myotonic dystrophy type 1 (DM1) is the most common form of muscular dystrophy in adults and affects mainly the skeletal muscle, heart, and brain. DM1 is caused by a CTG repeat expansion in the 3′UTR region of the DMPK gene that sequesters muscleblind-like proteins, blocking their splicing activity and forming nuclear RNA foci. Consequently, many genes have their splicing reversed to a fetal pattern. There is no treatment for DM1, but several approaches have been explored, including antisense oligonucleotides (ASOs) aiming to knock down DMPK expression or bind to the CTGs expansion. ASOs were shown to reduce RNA foci and restore the splicing pattern. However, ASOs have several limitations and although being safe treated DM1 patients did not demonstrate improvement in a human clinical trial. AAV-based gene therapies have the potential to overcome such limitations, providing longer and more stable expression of antisense sequences. In the present study, we designed different antisense sequences targeting exons 5 or 8 of DMPK and the CTG repeat tract aiming to knock down DMPK expression or promote steric hindrance, respectively. The antisense sequences were inserted in U7snRNAs, which were then vectorized in AAV8 particles. Patient-derived myoblasts treated with AAV8. U7snRNAs showed a significant reduction in the number of RNA foci and re-localization of muscle-blind protein. RNA-seq analysis revealed a global splicing correction in different patient-cell lines, without alteration in DMPK expression.